Parametric optimization of fatigue behaviour of hybrid aluminium metal matrix composites. (2020) - Moona, Girija; Walia, R.S.; Rastogi, Vikas; Sharma, Rina
Abstract: For various aerospace applications aluminium has emerged as most preferred material due to desirable attributes such as superior strength to density ratio, greater specific strength, better corrosion resistance, high toughness and cost effectiveness. The most desirable characteristics for aerospace materials are ability to withstand elevated temperature and sustain higher fatigue loadings. Current experimental investigation was carried out to explore and optimize fatigue characteristics of hybrid composites developed by infusing particulate reinforcements into aluminium alloy. Eggshell particles (wt% 0.5, 1 and 1.5, average particle size ≈ 60 µm), Silicon Carbide particles (wt% 1, 1.5 and 2, average particle size ≈ 65 µm) and Aluminium Oxide particles (wt% 1.5, 2 and 2.5, average particle size ≈ 90 µm) were reinforced into Al 7075-T6 metal matrix through electromagnetic stir casting route as per L9 orthogonal array of Taguchi's approach in order to synthesize hybrid aluminium metal matrix composites with enhanced fatigue resistance. Analysis of variance (ANOVA) was also conducted to observe the effect of different process parameters on fatigue life of developed composites. Nine hybrid composite specimens and one as-cast Al7075 -T6 specimen (in three replications) were prepared in accordance with ASTM E 468/606 and were evaluated for low cycle fatigue resistance at a constant load of 2 kg and constant speed of 500 rpms on rotating beam fatigue testing machine. It was observed that at 30 °C temperature, hybrid composite specimens exhibited significant enhancement in fatigue resistance in terms of reversible load cycles survived. The as-cast Al 7075-T6 specimen sustained only 94 load cycles while the highest number of load cycles i.e. 4560 were survived by hybrid composite specimen with Al 7075-T6 as base metal reinforced with 1.5 wt% of eggshell particles, 1.5 wt% of SiC particles and 1.5 wt% of Al2 O3 particles (total reinforcement content only 4.5%) and mechanically stirred for 360 s.